Onsite Sewage Treatment and Disposal Systems: Bacteria and Protozoa - Mary Lusk; Gurpal S. Toor; Tom Obreza (EDIS)
Keeping disease-causing microorganisms out of groundwater used for drinking water supplies is important to protect human health. This 7-page fact sheet reports the sources of bacteria and protozoa in wastewater, discusses diseases associated with drinking water contaminated with wastewater, and then details their fate in septic systems. Written by Mary Lusk, Gurpal S. Toor, and Tom Obreza, and published by the UF Department of Soil and Water Science, July 2011. (Photo by Tara Piasio)